Progenitor diversity and neural cell specification in the central nervous system - Marcos R. Costa (Frontiers Research Topics, 2015)
The central nervous system continuously perceives, integrates, processes and generates information. These complex functions rely on the detailed elaboration of its cellular network and on the myriads of individual, highly differentiated and specialized cell types, classically subdivided into neurons, astrocytes and oligodendrocytes. The specification of these individual populations begins early during development with less differentiated, yet already partly restricted, progenitor cells. Anatomically located in dedicated germinative niches, neural progenitors perceive the influence of diffusible molecules of various natures and concentrations. These signals result in the initial specialization of cohorts of progenitors that express unique combinations of transcription factors. It is now clearly established that both extrinsic and intrinsic signals act in concert to determine the fate potentials of these progenitor cohorts. This limitation increases over time, adult neural progenitors being more restricted than their developmental counterparts. Nevertheless, recent data have shown that the fate restriction of neural progenitors, as well as that of their progenies, can be overwritten upon selected intrinsic factor expression, not only during development but also in adulthood. This e-book is a collection of original research studies along with review articles that, together, provide insights into the vast spatiotemporal diversity of neural progenitors, and the various factors that govern their fate potential.